Assessment Of Scholarly Discourse In An Esp Context:Case Of Research-Based Biology Articles At The University Of Tlemcen (مجلة الواحات للبحوث والدراسات, 2026)
This study investigates the assessment of scientific discourse within the framework of English for Specific Purposes (ESP), focusing on biology teachers at the University of Tlemcen. It identifies the challenges they face in meeting international publication requirements and demonstrates that writing assessment is an effective tool for determining linguistic and rhetorical needs. Using a mixed-method approach that combines quantitative and qualitative data, the findings highlight the importance of precise analyses to address these needs. The study proposes context-sensitive strategies and explicit criteria aimed at enhancing clarity, coherence, and overall quality in academic writing related to biology.